Osteoma periférico mandibular: reporte de caso y revisión de literatura - Oviedo, Jorge (2014)
Osteomas are benign osteogenic lesions arising from well differentiated mature bone. According to its location, they can be classified as peripheral, central, and extraskeletal; whereby the peripheral is most common. They are very rare in maxillary bones and there is no tendency for specific gender or age. They show a slow, progressive, and asymptomatic growth. CASE REPORT: A 71 year old male patient shows an increase of volume in the right mandibular bone, hard, asymptomatic, increasing over a period of 30-years. The images revealed the existence of a radiopaque lesion that was pedunculated and well defined; and, together with an incisional biopsy, showed the presence of a peripheral osteoma. Treatment consisted of total removal of the lesion. DISCUSSION: Only 86 cases of mandibular peripheral osteomas have been described in the specialized maxillofacial literature. Its most frequent location in the jawbone is the lingual surface and the inferior edge of the mandible. Rarely, as it was our case, it is located in the vestibular surface of the bone. The exact etiophatogenesis is still unknown, however it has been suggested as due to both neoplastic and reactional causes. A panoramic x-ray and a computerized tomography were used to determine the location and extension of the lesion. According to its size and symptomatology the treatment can be surgery or conservative. There are no reference to malignant disruption in the literature. Only one case of the group had recurrence. CONCLUSION: Maxillary peripheral osteomas are rare pathological entities. The lesions of bigger size, as the one showed here, have the potential to cause maxillary deformities of aesthetic and functional relevance that require surgical treatment.